If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (y + -1) + y = 11 Reorder the terms: (-1 + y) + y = 11 Remove parenthesis around (-1 + y) -1 + y + y = 11 Combine like terms: y + y = 2y -1 + 2y = 11 Solving -1 + 2y = 11 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 2y = 11 + 1 Combine like terms: -1 + 1 = 0 0 + 2y = 11 + 1 2y = 11 + 1 Combine like terms: 11 + 1 = 12 2y = 12 Divide each side by '2'. y = 6 Simplifying y = 6
| 6x^2+6x+6=14x+14 | | 1x-9=14 | | -(68c+38d+8)= | | -6x-y+3xy=18 | | x^2-3.5X+3.0625=1.0625 | | -6x-y+3xy-18=0 | | 3d+4=2+3d+0.5 | | 7x-(4x+2)= | | 2a+6=3 | | 22=2x-8 | | 6-3(6)= | | w-6-12=-8 | | 3a+7b=23 | | 1x=7 | | 4t=56 | | 2(-3)+[5(-5)]= | | m=-7(6-5) | | =-7(6-5) | | x^2-20x-9900=0 | | (9x-6)+3=(14x+28) | | (7-1)(5-8)= | | -20+3t=65 | | -16x^2-y+1156=0 | | -16x^2-x+1156=0 | | -20+3t=-65 | | 4p/3-p/4=6+5p/6 | | (10-3x)=(50x) | | x-(2x-1)=3 | | 4a+8c=16 | | x^2-2.6x-3.12=0 | | 6a+12q=18 | | x/7+x/6=39 |